(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Illumination, understanding of national mentality, historical facts, revelation of the true essence. The question of the unity of the universe and man. The main features of the creative process. The most delicate feelings, the depiction of nature in illuminating the national mentality, the creation of an image in the work of Shavkat Rahman, and the expression of figurative imagery in the work of the poet.